Materials with low DC magnetic susceptibility for sensitive magnetic measurements. (29th December 2015) - Khatiwada, R; Dennis, L; Kendrick, R; Khosravi, M; Peters, M; Smith, E; Snow, W M
Abstract: Materials with very low DC magnetic susceptibility have many scientific applications. To our knowledge however, relatively little research has been conducted with the goal to produce a totally nonmagnetic material. This phrase in our case means after spatially averaging over macroscopic volumes, it possesses an average zero DC magnetic susceptibility. We report measurements of the DC magnetic susceptibility of three different types of nonmagnetic materials at room temperature: (I) solutions of paramagnetic salts and diamagnetic liquids, (II) liquid gallium–indium alloys and (III) pressed powder mixtures of tungsten and bismuth. The lowest measured magnetic susceptibility among these candidate materials is in the order of 10 −9 cgs volume susceptibility units, about two orders of magnitude smaller than distilled water. In all cases, the measured concentration dependence of the magnetic susceptibility is consistent with that expected for the weighted sum of the susceptibilities of the separate components within experimental error. These results verify the well-known Wiedemann additivity law for the magnetic susceptibility of inert mixtures of materials and thereby realize the ability to produce materials with small but tunable magnetic susceptibility. For our particular scientific application, we are also looking for materials with the largest possible number of neutrons and protons per unit volume. The gallium–indium alloys fabricated and measured in this work possess to our knowledge the smallest ratio of volume magnetic susceptibility to nucleon number density per unit volume for a room temperature liquid, and the tungsten-bismuth pressed powder mixtures possess to our knowledge the smallest ratio of volume magnetic susceptibility to nucleon number density per unit volume for a room temperature solid. This ratio is a figure of merit for a certain class of precision experiments that search for possible exotic spin-dependent forces of Nature.